The locus coeruleus and central chemosensitivity - Gargaglioni, Luciane H. [UNESP]; Hartzler, Lynn K.; Putnam, Robert W. (Elsevier B.V., 2010)
The locus coeruleus (LC) lies in the dorsal pons and supplies noradrenergic (NA) input to many regions of the brain, including respiratory control areas. The LC may provide tonic input for basal respiratory drive and is involved in central chemosensitivity since focal acidosis of the region stimulates ventilation and ablation reduces CO(2)-induced increased ventilation. The output of LC is modulated by both serotonergic and glutamatergic inputs. A large percentage of LC neurons are intrinsically activated by hypercapnia. This percentage and the magnitude of their response are highest in young neonates and decrease dramatically after postnatal day P10. The cellular bases for intrinsic chemosensitivity of LC neurons are comprised of multiple factors, primary among them being reduced extracellular and intracellular pH, which inhibit inwardly rectifying and voltage-gated K(+) channels, and activate L-type Ca(2+) channels. Activation of K(Ca) channels in LC neurons may limit their ultimate response to hypercapnia. Finally, the LC mediates central chemosensitivity and contains pH-sensitive neurons in amphibians, suggesting that the LC has a long-standing phylogenetic role in respiratory control. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Rodent; Amphibian; respiration; Chemosensitive signaling; Serotonin; Glutamate; K channel; Hypercapnia; Development